Governance Of The Kosambi Traditional Market In Bandung City - Nteseo, Yetty; Kushendar, Deden Hadi (Economics and Digital Business Review, 2023)
This article examines the governance structure and practices employed in the management of the Kosambi Traditional Market in Bandung. Traditional markets, as essential components of urban economies, face unique challenges in maintaining relevance amid evolving consumer preferences and urban development. Through a comprehensive case study of the Kosambi Traditional Market, this research investigates the governance mechanisms in place, focusing on decision-making processes, stakeholder engagement, and regulatory frameworks. The study employs a mixed-methods approach, combining qualitative interviews with market stakeholders, local authorities, and vendors, along with quantitative analysis of market performance indicators. By evaluating the effectiveness of the current governance model, the research aims to identify strengths, weaknesses, and opportunities for improvement. Insights gained from this study contribute to the broader discourse on market governance, providing valuable lessons for policymakers, urban planners, and market administrators. As traditional markets play a vital role in preserving cultural heritage and supporting local economies, understanding and enhancing their governance structures become imperative for sustained viability. The findings of this research offer practical recommendations for optimizing the governance of traditional markets, with implications for the revitalization of similar markets nationwide. This study contributes to the academic literature on public administration and market management, particularly in the context of cultural heritage preservation and sustainable urban development.